Digitization as one of the methods of assessing the number and distribution of small water bodies - Golus Włodzimierz; Markowski Maciej (Oceanological and Hydrobiological Studies)
Small water bodies (ponds) are a widespread component of the landscape; however, their exact number is often estimated by their small size, temporal variability, or being invisible due to dense vegetation cover. Their distribution is typically assessed through the analysis of aerial and satellite imagery. Nevertheless, a more traditional but labor-intensive approach—manual digitization from topographic maps—has been considered highly precise. In an area of 12 400 km2 in northern Poland, nearly 32 000 ponds were digitized, with their occurrence strongly linked to geomorphological units. While they are most abundant in moraine plateaus, ponds are present across all post-glacial landscapes. Additionally, the authors observed that although pond distribution appears largely random, some exhibit distinct spatial patterns, forming linear chains or clustered groups.